2014
DOI: 10.1016/j.semcdb.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Licensing of DNA replication, cancer, pluripotency and differentiation: An interlinked world?

Abstract: Recent findings provide evidence for a functional interplay between DNA replication and the seemingly distinct areas of cancer, development and pluripotency. Protein complexes participating in DNA replication origin licensing are now known to have roles in development, while their deregulation can lead to cancer. Moreover, transcription factors implicated in the maintenance of or reversal to the pluripotent state have links to the pre-replicative machinery. Several studies have shown that overexpression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 129 publications
0
45
0
Order By: Relevance
“…Different cyclin-CDK combinations specifically determine the downstream targeted proteins that in turn promote the expression of cyclins and enzymes required for DNA replication (6). Previous studies showed that disregulation of the cell cycle components may cause the tumor cell to multiply uncontrollably, which finally leads to tumor formation (7). Importantly, therapies targeting CDK inhibitor present a favorable prospect in the treatment of a variety of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Different cyclin-CDK combinations specifically determine the downstream targeted proteins that in turn promote the expression of cyclins and enzymes required for DNA replication (6). Previous studies showed that disregulation of the cell cycle components may cause the tumor cell to multiply uncontrollably, which finally leads to tumor formation (7). Importantly, therapies targeting CDK inhibitor present a favorable prospect in the treatment of a variety of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In connection with cell growth, the cell cycle that is the series of events that take place in a cell leading to its division into two daughter cells is a vital process for development and organ renewal and is elaborately regulated by cell cycle checkpoint components. However, cancer cells abnormally proliferate by active cell division due to a dysregulation of the cell cycle components [ 20 ] . In addition, the EMT process is an important cellular mechanism by which epithelial cells lose their cell polarity and cell-cell adhesion, instead gaining an migratory and invasive mesenchymal phenotype [ 2122 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of cell cycle components may cause the cell to multiply uncontrollably, thus leading to tumor formation (Champeris Tsaniras et al, 2014), as is the case for GBM (Hazane-Puch et al, 2015;Xie et al, 2015). Various studies have shown that the cell cycle pathway and cell cycle-related molecules can be considered therapeutic targets of many cancers (Rao, 1996;Newman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%